З’ясування нейрофізіологічних та вегетативних механізмів забезпечення переробки інформації в здорових і глухих людей - Юхименко, Лілія; Yukhimenko, Lilia (Східноєвропейський національний університет імені Лесі Українки, 2017)
Отримано відмінні нейрофізіологічні та вісцеральні кореляти переробки інформації в здорових і глухих людей. Глухі й здорові особи відрізняються рівнями напруження механізмів регуляції серцевого ритму, «фізіологічної ціни», патернами мозкової активності, нейрофізіологією впізнання стимулів та результативністю виконання завдання. The research results of characteristics of information processing by the higher divisions of the Central nervous system and peculiarities of neurophysiological and autonomic mechanisms of information processing in healthy and deaf patients were represented. The differences in neurophysiological and vegetative correlates of information processing in people with different status of auditory function were established. It was revealed that the deaf and healthy examined were differed according to the voltage levels of the mechanisms of heart rate regulation, «physiological price», activation of stress-realizing mechanisms, amplitude patterns of brain activity, neurophysiology identification of the incentives and performance of the working efficiently. The obtained results complement the limitations of diagnosis, correction and prevention of cognitive disorders and psychosomatic pathology
The Study of the Neurophysiological and Autonomic Mechanisms for Information Processing in Healthy and Deaf People.
Keywords: переробка інформації; депривація слуху; нейрофізіологічні механізми; вегетативні механізми; information processing; deprivation of hearing; autonomic mechanism; neurophysiological mechanism